DEVELOPMENT OF COMIC LEARNING MEDIA TO IMPROVE STUDENT’S CONCEPT UNDERSTANDING AND LEARNING INDEPENDENCE - Laili Ulviah; Salamun Hadi Subroto; Oriza Satifah (JIP Jurnal Ilmiah PGMI, 2021)
This research aims to produce learning media in the form of science comic that can improve conceptual understanding and learning independence of class VI students. This development research adapts the development of 4- D model media, but only until the Develop stage. The trial design carried out is the validation test of material experts and media experts as well as teachers, limited trials and field trials. The data collection instruments use questionnaires, question sheets and validation sheets to obtain qualitative and quantitative data. The questionnaires and questions used to collect the data are also validated first. The results show that the media developed by experts is in the "very good" category, the student assessments show that this media are practical and efficient for learning so that the media is feasible to use. The results of the field test based on the data analysis, the effect-size value of concept understanding of 0.758 is in the high criterion, and the learning independence of 0.540 is in the high criterion. These results according to the effect-size analysis mean that learning media in the form of science comic can improve conceptual understanding and learning independence of class VI students in the high category.